Malaysian telecommunication customer voice retaliation from dissatisfied service experience: the mediating effect of negative emotion / Nor Irvoni Mohd Ishar - Mohd Ishar, Nor Irvoni (2018)
Understanding customer complaining behaviour is imperative in the current economic condition as it could serve as a signal to the deteriorating performance of any organisation. It is much more crucial for service organisation because customers tend to move from one organisation to another when dissatisfaction persists. What may worsen the situation is that customers do not only just complain, but they retaliate. For retaliation to surface, it requires a specific trigger, the emotion. Therefore, the aim of this study is to investigate the concept of customer retaliation in relation to dissatisfying service experience with the interplay of emotion. The study investigates the relationship between the three variables, and the mediation effect of negative emotional experience on the relationship between dissatisfied service experience and subscribers voice retaliation behaviour. Despite extensive research conducted on the topic, understanding on its overall concept is still scarce, over simplified, and does not reflect the full spectrum of the subject. Many of the studies conducted have been focusing only on certain aspects of behavioural responses, i.e. switch and negative word-of-mouth, and overlooks other possible aggressive response such as retaliation. Important pertinent concepts such as emotions are ignored, thus creating a knowledge vacuum as it fails to highlight the severity of such behaviour. These voids leave researchers and practitioners, with limited information in understanding the full spectrum of complaining responses. Therefore, it is imperative that voice retaliation be further investigated. Such an understanding is likely to enhance the existing body of knowledge on how dissatisfaction can be dealt with effectively, and a model of coping with dissatisfaction and retaliation can be conceptualized and tested. The population of the current study comprises of mobile telecommunication service subscribers who have experienced service dissatisfaction and must to some extent performed some form of complaining behaviours. This quantitative method of study used questionnaires as the instrument to collect data. On a four-point Likert-rating scale, sixty-six items from three variables formed the basis of the instrument. The instrument was distributed to 150 subscribers using a mall intercept method. A total of 108 (72%) responses were used in the final analysis. A hybrid method of data analysis was employed in this study. First, the Rasch Measurement analysis was used to test for internal validity and reliability of the items, and produces an interval measurement unit known as logits. Then, the Rasch logits measures were imputed into the SmartPLS3 software where analysis on hypotheses were conducted using the Structural Equation Model approach. Empirical evidence revealed that; (i) Rasch Analysis is a robust procedure, and hence validates the psychometric properties of the instrument, (ii) dissatisfying service experience positively influence voice retaliation behaviours, (iii) dissatisfactory service experience positively influence negative emotional experience, (iv) negative emotional experience positively influence voice retaliation behaviour, and (iv) negative emotional experience mediates the relationship between dissatisfied service experience and voice retaliation behaviour. Therefore, it is concluded that customer's emotion is a crucial element that service provider must pay attention to, when dealing with service dissatisfaction and customer response behaviour. The outcome of this study has provided support that emotion does play an important significant role in the customer - service provider relationship, and if not attended properly, may have the tendency to create a lot of damage to the organisation.